Targeted sanctions : the impacts and effectiveness of United Nations action - Biersteker, Thomas J.,; Eckert, Sue E.,; Tourinho, Marcos, (Cambridge University Press, 2016)
International sanctions have become the instrument of choice for policymakers dealing with a variety of different challenges to international peace and security. This is the first comprehensive and systematic analysis of all the targeted sanctions regimes imposed by the United Nations since the end of the Cold War. Drawing on the collaboration of more than fifty scholars and policy practitioners from across the globe (the Targeted Sanctions Consortium), the book analyzes two new databases, one qualitative and one quantitative, to assess the different purposes of UN targeted sanctions, the Security Council dynamics behind their design, the relationship of sanctions with other policy instruments, implementation challenges, diverse impacts, unintended consequences, policy effectiveness, and institutional learning within the UN. The book is organized around comparisons across cases, rather than country case studies, and introduces two analytical innovations: case episodes within country sanctions regimes and systematic differentiation among different purposes of sanctions.